The Incidence of Pulmonary Tuberculosis in HIV/AIDS Patients at Deli Serdang Regional General Hospital, 2013–2015 - Soniya Krishna; Parluhutan Sigian; Surjit Singh (Jurnal Kedokteran Methodist, 2024)
Background: In 2010, the number of TB patients rose to 330,000 and in2012, the number of TB patients is quite sharp, ie 583,000 people. TB isthe number one killer among infectious diseases and ranking third in thelist of top ten diseases in Indonesia which causes about 100,000 deathsannually, or in a day occurred 300 deaths due to TB.Methods: This study is a descriptive and cross sectional study conductedat the Medical Records Regional General Hospital Deli Serdang years2013-2015 total of 49 samples were selected with a total samplingtechnique.Results: Based on the research that has been done, the highest age groupwith pulmonary tuberculosis in people with HIV / AIDS is as much as32.65% of 25-30 years, by sex more dominant male is 79.59%, based onthe most common residence is outside city field as much as 83.67%, thehighest frequency based on the self- employed work is as much as 38.77%,the highest frequency of risk factors based on sex is as much as 71.42%and the highest frequency based on CD4 count is <200 as much as91.83%.Conclusion: Based on this study concluded that the incidence ofpulmonary TB in people with HIV / AIDS are still very high, the highest inthe age group 25-30 years of age and male gender, the dominantoccupation were self-employed, the highest risk factor was sexual relationswith CD4 count <200.